Foreign Body in Preauricular Region - Gaetti-Jardim, Ellen Cristina [UNESP]; dos Santos, Pamela Leticia [UNESP]; Guskuma, Marcos Heidy [UNESP]; Magro Filho, Osvaldo [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP]; Ponzoni, Daniela [UNESP]; Aranega, Alessandra Marcondes [UNESP]; Shinohara, Elio Hitoshi [UNESP] (Lippincott Williams & Wilkins, 2011)
Foreign bodies, although they are often found throughout the body, to a lesser degree in the face, still constitute a diagnostic challenge for the trauma surgeon. Its removal means danger of damaging important facial anatomic structures, even if its exact position from the image data was known. So, the objective is to describe a clinical report of a patient (42 years of age, male sex) who experienced falling to the ground, attended by the Department of Surgery and Traumatology Bucco-Maxillo-Facial Surgery, Faculty of Dentistry of Aracatuba, São Paulo State University, and 2 days after the trauma, he reported difficulty in mouth opening and pain. After clinical evaluation, we observed the presence of injury in the left preauricular region already in the process of healing. During the intraoral physical examination, a limitation of the mouth opening was noted. Radiographic posteroanterior and profile of the face showed 2 radiopaque foreign bodies in the left side, lying apparently at the region of the mandibular condylar process. Under local anesthesia, foreign body removal was carried from there with access to it through the preexisting facial injury. Further clinical examinations showed an improvement in mouth opening, absence of pain complaints, and/or functional complaints.
Keywords: Face; wounds; injuries; foreign bodies